Study of PCDTBT: PC71BM nanocomposite via template assisted method for humidity sensing application / Nor Asmaliza Bakar - Nor Asmaliza , Bakar (2018)
The quest for materials with molecular scale properties has led to the development of one-dimensional (1D) nanostructures. Both solution and melt-assisted template provides a simple and cost-effective method for fabrication of 1D nanostructures. This method has been used to fabricate various types of nanostructures with different morphological, optical and structural properties. However, the parameters and principles that govern the final properties still remain ambiguous. This research aims to investigate the involved parameters and infiltration techniques and develop an understanding of the nanostructure formation mechanism. The effect of spinning rate, polymer solution concentration and temperature have also been evaluated. In the first phase, Poly [N-9′-heptadecanyl- 2,7- carbazole- alt- 5, 5- (4′, 7′- di- 2- thienyl- 2′, 1′, 3′- benzothiadiazole)] (PCDTBT) nanostructures are formed via the porous alumina template of three different infiltration techniques; spin coating, immersion and combination of drop casting & annealing technique. Different solution concentrations of 5, 10 and 15 mg/ml have been evaluated for all the three techniques. For spin coating technique, PCDTBT was deposited onto the alumina template using 1000, 2000 and 3000 rpm spinning rate. PCDTBT nanotubes were successfully grown by immersing the porous alumina template (immersion technique) into 5, 10 and 15 mg/ml PCDTBT solution for 2, 12 and 24 hours followed by annealing at 50 and 150°C. In the combination of drop casting and annealing technique, PCDTBT nanostructures were prepared via porous alumina template by varying the solution concentrations (5, 10 and 15 mg/ml) and annealing temperatures (300, 350 and 400 C) which are above the PCDTBT melting point. Changes in morphological, optical and structural properties among nanostructures at different concentrations, spinning rate, infiltration time and annealing temperature have been studied using Field Emission Scanning Electron Microscope (FESEM), Ultraviolet-visible (UV–vis), Photoluminescence (PL) and Raman spectroscopy. The correlation between the parameters involved was also investigated. PCDTBT nanostructures that produced at optimum processing parameters demonstrated more enhanced morphological, structural and optical properties. In the second phase, several selected parameters from the first phase were used to synthesise the p-n junction composite of [N-90-hepta-decanyl-2, 7-carbazole-alt-5, 5-(40, 70-di-2-thie-nyl 20, 10,30benzothiadiazole)] (PCDTBT): [6, 6]-phenyl C71-butyric acid methyl ester (PC71BM). PCDTBT nanostructures were first produced followed by the infiltration of PC71BM. Formation of p-n junction composite was elaborated in which its morphological, optical and structural properties were compared over its p-type counterparts. In the third phase, PCDTBT:PC71BM composite nanostructures was used as an active layer in the capacitive type humidity sensor (Al/PCDTBT:PC71BM/Al). The humidity sensing characteristics of the sensor were investigated by exposing the organic active layer to a wide range relative humidity (%RH) levels at room temperature. Different morphological properties exhibited by each of the nanostructures from different techniques contributed to different abilities of the sensors. PCDTBT:PC71BM composite nanostructures produced from immersion technique showed significantly higher sensitivity ~62.34 pF/ %RH as compared to the spin coating and combination of drop casting & annealing technique. The ideal capacitive sensors showed the desirable reproducibility, acceptable hysteresis (~11 %), faster response (10 s) and recovery (5 s) time.